Analisis Penerimaan E-Tax Ditjen Pajak Kota Palembang Menggunakan Technology Acceptance Model (TAM) - Adellia Rahmawati; Dien Novita; Iis Pradesan (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The Regional Tax Management Agency has the task of supervising taxpayers not to make deviations. The taxpayers must fulfill their tax obligations correctly and on time. To minimize fraud that occurs and make it easier to manage taxpayers. E-Tax can be used to simplify the online taxation process. This study aims to determine the factors that affect the acceptance of E-Tax with the Technology Acceptance Model (TAM) method. The data collection process used the interview method, literature study, and questionnaires distributed to taxpayers registered with the Regional Tax Management Agency of Kemuning Palembang District, the sample amounting to 32. The data analysis technique used in this research is the quantitative data analysis method. Data analysis in this study used Structural Equation Modeling (SEM). Using the Technology Acceptance Model (TAM), the analysis results show that taxpayers registered with the Palembang City Regional Tax Management Agency. The respondents in this study accept E-Tax, which facilitates the tax process in the restaurant, parking, entertainment, and hotel sectors. The acceptance of the results in five of the six hypotheses.